Changes in Theory-Based Psychological Factors Predict Weight Loss in Women with Class III Obesity Initiating Supported Exercise - James J. Annesi; Srinivasa Gorjala (Hindawi Limited, 2010)
Background. Psychological factors' effect on weight loss is poorly understood, in general, and specifically in the severely obese. Objective. To examine whether a behavioral model based on tenets of social cognitive and self-efficacy theory will increase understanding of the relationship between exercise and weight loss. Methods. Fifty-one women with severe obesity participated in a 24-week exercise and nutrition information treatment and were measured on changes in psychological factors and exercise attendance. Results. A significant portion of the variance in BMI change (adjusted for number of predictors) was accounted for by the behavioral model (𝑅2adj=0.23). Entry of exercise session attendance only marginally improved the prediction to 0.27. Only 19% of the weight lost was directly attributable to caloric expenditure from exercise. Conclusions. Findings suggest that participation in an exercise program affects weight loss through psychological pathways and, thus, may be important in the behavioral treatment of severe obesity.